Brain-derived neurotrophic factor modulates immune reaction in mice with peripheral nerve xenotransplantation - Yu X; Lu L; Liu Z; Yang T; Gong X; Ning Y; Jiang Y (Neuropsychiatric Disease and Treatment)
Xin Yu,1 Laijin Lu,1 Zhigang Liu,1 Teng Yang,2 Xu Gong,1 Yubo Ning,3 Yanfang Jiang4 1Department of Hand Surgery, 2Department of Orthopedics, The First Hospital of Jilin University, Changchun, 3Department of Orthopedics, Ningshi Orthopedics Hospital of Tonghua, Tonghua, 4Department of Central Laboratory, The First Hospital of Jilin University, Changchun, People’s Republic of China Background: Brain-derived neurotrophic factor (BDNF) has been demonstrated to play an important role in survival, differentiation, and neurite outgrowth for many types of neurons. This study was designed to identify the role of BDNF during peripheral nerve xenotransplantation. Materials and methods: A peripheral nerve xenotransplantation from rats to mice was performed. Intracellular cytokines were stained for natural killer (NK) cells, natural killer T (NKT) cells, T cells, and B cells and analyzed by flow cytometry in the spleen of the recipient mouse. Serum levels of related cytokines were quantified by cytometric bead array. Results: Splenic NK cells significantly increased in the xenotransplanted mice (8.47±0.88×107 cells/mL) compared to that in the control mice (4.66±0.78×107 cells/mL, P=0.0003), which significantly reduced in the presence of BDNF (4.85±0.87×107 cells/mL, P=0.0004). In contrast, splenic NKT cell number was significantly increased in the mice with xenotransplantation plus BDNF (XT + BDNF) compared to that of control group or of mice receiving xenotransplantation only (XT only). Furthermore, the number of CD3+ T cells, CD3+CD4+ T cells, CD3+CD4- T cells, interferon-γ-producing CD3+CD4+ T cells, and interleukin (IL)-17-producing CD3+CD4+ T cells, as well as CD3-CD19+ B cells, was significantly higher in the spleen of XT only mice compared to the control mice (P<0.05), which was significantly reduced by BDNF (P<0.05). The number of IL-4-producing CD3+CD4+ T cells and CD3+CD4+CD25+Foxp3+ T cells was significantly higher in the spleen of XT + BDNF mice than that in the spleen of XT only mice (P<0.05). Serum levels of IL-6, TNF-α, interferon-γ, and IL-17 were decreased, while IL-4 and IL-10 were stimulated by BDNF following xenotransplantation. Conclusion: BDNF reduced NK cells but increased NKT cell accumulation in the spleen of xenotransplanted mice. BDNF modulated the number of splenic T cells and its subtype cells in the mice following xenotransplantation. These findings suggest that BDNF inhibits rejection of peripheral nerve following xenotransplantation by regulating innate as well as adaptive immune reaction. Keywords: peripheral nerve, xenotransplantation, brain-derived neurotrophic factor